Comparison of dexmedetomidine, lidocaine and fentanyl in attenuation of haemodynamic response to laryngoscopy and intubation in cardiac surgery patients - Karthik Kateel; Indu Verma; Manbhavan Mahajan (Creative Pharma Assent, 2023)
Objective: Laryngoscopy and intubation produce sympathoadrenal response posing risk especially in cardiac patients due to arrhythmias, myocardial ischemia increasing morbidity and mortality. Our aim is to compare lidocaine, fentanyl and dexmedetomidine in attenuation of this response in cardiac surgery patients. Material and Methods: Ninety patients were allocated into 3 groups of 30 participants each. Group A obtained 1µg/kg Dexmedetomidine for 10 minutes before laryngoscopy. Group B 1.5mg/kg of Lidocaine and Group C 2µg/kg Fentanyl 90 seconds before intubation. Hemodynamic parameters like Heart rate (HR), Systolic Blood Pressure (SBP), Diastolic Blood Pressure (DBP), Mean Arterial Pressure (MAP) and Rate Pressure Product (RPP) were noted before intubation and 1,3,5,10 and 15 minutes after intubation. Statistical analysis was done using Epi info version 7.2.1.0 statistical software (Chi square test, ANOVA test). Results: Dexmedetomidine had significant reduction in SBP at 1st (p-value=0.003), 5th, 10th and 15th (p-value<0.001) minute and in DBP at 3rd, 5th, 10th and 15th (p-value< 0.001). MAP was significantly reduced with dexmedetomidine at 1st, 3rd, 5th, 10th and 15th minute (p-value</ = 0.001) and RPP at 1st (p-value=0.040), 3rd (p-value=0.001), 5th (p-value=0.001), 10th (p-value<0.001) and 15th(p-value=0.002) minute. Dexmedetomidine had higher fall in HR at 1st, 3rd, 5th, 10th mins which was not statistically significant(p-value>0.05). Conclusion: Dexmedetomidine 1µg/kg given as 10 min infusion before laryngoscopy was more effective than fentanyl and lidocaine in blunting hemodynamic response to laryngoscopy and intubation in cardiac surgery patients. However due to significant hypotension associated with dexmedetomidine, it has to be used with caution in these patients.